Identification of barley genotypes with higher protein content coupled with bold grains for food and malt barley improvement under sub-tropical climates - Kumar, Dinesh; Verma1, RPS; Narwal, Sneh; Singh, Jogendra; kumar, Vishnu; Kharub, Ajit Singh; Singh, Gyanendra Pratap (Journal of Cereal Research, 2017)
Grain protein content is very important trait with respect to barley grains meant for food, feed and malt purposes. Barley grain protein content was evaluated in several genotypes for two years at different locations under sub-tropical climates in India. The grain protein content was affected both by the genotype (varied from 11.4-14.7% dwb during 2012-13 and 9.9-15.4 % dwb during 2013-14) and growing location (varied from 10.5-15.5 % dwb during 2012-13 and 11.4-15.1 % during 2013-14). The genotypes with unique combination of moderately higher protein content coupled with plump grains were identified. These genotypes can be useful resources for malt barley improvement programme, meant for food purposes under sub-tropical climates having relatively shorter grain filling duration. Â Doi.org/10.25174/2249-4065/2017/73253